PENGARUH HAFALAN AL-QUR'AN TERHADAP KUALITAS SPIRITUAL PESERTA DEWASA DI LEMBAGA BIMBINGAN AL-QUR'AN RISALATUNA JAKARTA SELATAN - Dhorifah; Fitriyani, Hawin; Andrianto, Dedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Qur'an memorization on the spiritual quality of adult participants at the Risalatuna Qur'an Guidance Institution, South Jakarta. The study was motivated by the assumption that memorizing the Qur'an can improve spiritual awareness, emotional calmness, worship discipline, and closeness to Allah. However, in practice, not all participants who memorize the Qur'an experience significant spiritual improvement. This research employed a quantitative correlational approach involving 40 adult participants selected through purposive sampling techniques. Data were collected using questionnaires on spiritual quality consisting of 24 statement items and supported by data on the participants’ level of Qur'an memorization. The collected data were analyzed using Pearson Product Moment correlation and simple linear regression analysis. The findings revealed that there was a positive relationship between Qur'an memorization and the spiritual quality of adult participants with a correlation coefficient value of 0.315, indicating a low relationship level. The significance value obtained was 0.051, which indicates that the relationship was not statistically significant at the 5% significance level, although it approached significance. The coefficient of determination showed that Qur'an memorization contributed 9.9% to the spiritual quality of participants, while the remaining 90.1% was influenced by other factors such as religious environment, worship habits, and psychological conditions. Therefore, Qur'an memorization still plays a role in improving spiritual quality, although it is not the dominant factor affecting spiritual development.